2022
DOI: 10.3390/s22207863
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Injected CO2 Using Earthquake Waves Measured by Downhole Fibre-Optic Sensors: CO2CRC Otway Stage 3 Case Study

Abstract: Monitoring changes of formation properties along the well bore associated with the presence of carbon dioxide can be important for both tracking the plume inside of the primary containment and detecting leakage into the zone located above the reservoir. This can be achieved with time lapse wireline logging, but this approach requires well intervention and is not always possible. If the well is permanently instrumented with an optical fibre, it can be used as a distributed seismic receiver array to detect gas b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…By assuming the values, σ C ∼ 30 mN=m and θ C ∼ 30°( see subsection 6.5 in Cook, 2014) and r C ∼ 10 μm, the minimum pressure inside the plume should be ∼5 kPa. This pressure may be sufficient to trigger the microseismic events on a critical fault adjacent to the Splay Fault 2, because it exceeds the strength of earth tides as well as the strongest ambient seismic noise signals at the site (Glubokovskikh et al, 2021;Shashkin et al, 2022) that have reactivated the seismogenic faults with lower critical pressure. In addition, Rothert and Shapiro (2007) showed that fluid-induced seismicity may be triggered by fluid pressure just above 1 kPa.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By assuming the values, σ C ∼ 30 mN=m and θ C ∼ 30°( see subsection 6.5 in Cook, 2014) and r C ∼ 10 μm, the minimum pressure inside the plume should be ∼5 kPa. This pressure may be sufficient to trigger the microseismic events on a critical fault adjacent to the Splay Fault 2, because it exceeds the strength of earth tides as well as the strongest ambient seismic noise signals at the site (Glubokovskikh et al, 2021;Shashkin et al, 2022) that have reactivated the seismogenic faults with lower critical pressure. In addition, Rothert and Shapiro (2007) showed that fluid-induced seismicity may be triggered by fluid pressure just above 1 kPa.…”
Section: Analysis Of the Resultsmentioning
confidence: 99%
“…We estimate the earthquakes magnitudes in CRC-3 and CRC-7 using a stacked P-wave wavelet in the interval 600-800 m true vertical depths. We chose this interval, because it features (1) relatively uniform formation stiffness and its effect on the amplitudes (Pevzner, Gurevich, et al, 2020;Shashkin et al, 2022); (2) most reliable travel-time picks with neither polarity flips nor interference of various wave modes;…”
Section: Estimation Of the Moment Magnitudementioning
confidence: 99%
“…DASs are installed in deep monitoring wells (CRC3-CRC7) to continuously collect seismic data, allowing for the inversion of CO 2 distributions based on DAS information. 56,57 Additionally, nine surface orbital vibrators (SOV1-SOV9) stimulate seismic signals daily for 2.5 h, recording scans performed through seismic detectors buried 3 m below the source. The data are automatically collected and processed on-site, achieving the goal of intelligent processing, with results available within 2 days.…”
Section: Co 2 Crc Otway Project Australiamentioning
confidence: 99%